A Comparative Study on Knowledge about Reproductive Health among Urban and Rural Women of Bangladesh. - Monoarul Haque (Journal of Family and Reproductive Health, 2015)
To compare the level of knowledge on reproductive health among urban and rural women of selected area of Bangladesh.A descriptive cross-sectional study was undertaken among 200 women selected purposively from different rural and urban areas of Bangladesh. Data were collected using a semi-structured interviewer-administered questionnaire by face to face interview. Knowledge level was analyzed according to poor, moderate and good knowledge by pre-defined knowledge scoring.Mean age of the respondents was 26 years and majority (66%) of them was housewives. Most of them (61%) had completed their primary level education. Around three-fourth of them belongs to lower-middle income group. Overall level of reproductive health knowledge was more evident among urban reproductive aged women than rural counterparts (p < 0.001). Moreover, significant knowledge gap was found regarding family planning (p = 0.005), care during pregnancy (p < 0.001), safe motherhood (p = 0.002), newborn care (p = 0.009) and birth spacing (p < 0.001) between urban and rural women. Family members were the major source of information in both groups.A wide knowledge gap was found between Bangladeshi urban and rural respondents regarding their reproductive behaviors. Government and concerned organizations should promote and strengthen various health education programs to focus on reproductive health, especially among reproductive aged women in rural area.